2011
DOI: 10.1016/j.bbadis.2011.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction mediated by quinone oxidation products of dopamine: Implications in dopamine cytotoxicity and pathogenesis of Parkinson's disease

Abstract: The study has demonstrated that dopamine induces membrane depolarization and a loss of phosphorylation capacity in dose-dependent manner in isolated rat brain mitochondria during extended in vitro incubation and the phenomena are not prevented by oxyradical scavengers or metal chelators. Dopamine effects on brain mitochondria are, however, markedly prevented by reduced glutathione and N-acetyl cysteine and promoted by tyrosinase present in the incubation medium. The results imply that quinone oxidation product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 70 publications
2
76
1
Order By: Relevance
“…Production of quinoproteins may inhibit plant growth through cross linking of membrane proteins, deactivation of enzymes, mitochondrial dysfunction, disrupting homeostasis and DNA fragmentation leading to apoptosis. [12][13][14]23) Previously, it has been reported that l-DOPA inhibited mitochondrial complex I (NADH dehydrogenase) and complex IV (cytochrome c oxidase) activities in rat and human mitochondria, respectively. 24,25) Moreover, quinoproteins from dopaminequinone induced mitochondrial swelling and permeability transition of the mitochondrial membrane and reduced complex I activity and electron transport leading to dysfunction of mitochondria in human and rat brains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Production of quinoproteins may inhibit plant growth through cross linking of membrane proteins, deactivation of enzymes, mitochondrial dysfunction, disrupting homeostasis and DNA fragmentation leading to apoptosis. [12][13][14]23) Previously, it has been reported that l-DOPA inhibited mitochondrial complex I (NADH dehydrogenase) and complex IV (cytochrome c oxidase) activities in rat and human mitochondria, respectively. 24,25) Moreover, quinoproteins from dopaminequinone induced mitochondrial swelling and permeability transition of the mitochondrial membrane and reduced complex I activity and electron transport leading to dysfunction of mitochondria in human and rat brains.…”
Section: Discussionmentioning
confidence: 99%
“…24,25) Moreover, quinoproteins from dopaminequinone induced mitochondrial swelling and permeability transition of the mitochondrial membrane and reduced complex I activity and electron transport leading to dysfunction of mitochondria in human and rat brains. 12,26,27) Recent proteomics studies using radiolabeled dopamine showed that dopaminequinone covalently modified critical proteins such as mitochondrial chaperonin, ubiquinol-cytochrome c reductase, mortalin, mitofilin, creatine kinase, and NADH dehydrogenase in animal and human cells. 28,29) The covalent modification of these proteins by dopaminequinone may contribute to cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies performed with chemical stressors showed evidence of temporal, response and dose concordance were conducted in vitro, the temporal concordance is difficult to establish; however, can be expected based on the well know temporal sequence of the two KEs. (Swedlow et al, 1996;Jha et al, 2000;Chinta et al, 2006;Marella et al, 2008;Hajieva et al, 2009;Du et al, 2010;Jana et al, 2011;Choi et al, 2014;Park et al, 2014) KE3 => KE4 PPPs, Parkinson's disease and childhood leukaemia The experimental support linking the degeneration of DA neurons of nigrostriatal pathways with the manifestation of motor symptoms of PD comes from human in vivo observations as well as from monkey, mice and rat in vivo models exposed to an experimental toxin i.e. rotenone and MPTP.…”
Section: A43 Empirical Supportmentioning
confidence: 99%
“…DA-dependent PC12 cell death, decline in the transmembrane potential and in intracellular ATP, and decline in complex II/III activities were observed and were all completely prevented by the presence of NAC. (Jana et al, 2011).…”
Section: A722 Empirical Support For Linkagementioning
confidence: 99%